Rapid detection of vesicular stomatitis virus New Jersey serotype in clinical samples by using polymerase chain reaction. - Rodriguez, L L (1993)
Vesicular stomatitis virus of the New Jersey serotype (VSV-NJ) causes vesicular disease in cattle, pigs, and horses throughout the Americas. Vesicular disease is clinically indistinguishable from foot-and-mouth disease (FMD). Therefore, outbreaks of vesicular disease in FMD-free areas must be rapidly diagnosed by laboratory methods and affected farms must be quarantined until laboratory results confirm the absence of FMD. Diagnosis is currently performed in high-containment (biosafety level 3) laboratories by using complement fixation and virus isolation in tissue culture. We describe here an alternative method for the detection of VSV-NJ RNA in clinical samples. This method includes a rapid acid guanidine-phenol RNA extraction procedure coupled with a one-tube polymerase chain reaction (PCR) using reverse transcriptase. By using this test, we were able to detect the largest number of positive samples (53 of 58), followed by complement (48 of 58) and isolation in tissue culture (43 of 58). The primers chosen for this assay amplify a 642-nucleotide region of the phosphoprotein gene of VSV-NJ but not of VSV-IN. Sequencing of the PCR product enables genetic typing of virus isolates and epidemiological studies. Since no infectious materials are necessary to perform this test and any infectious virus in clinical samples is destroyed by acid guanidine-phenol treatment, diagnosis can be safely performed in regular diagnostic laboratories.